Stolen decades: The unfulfilled expectations of the Belarusian economic miracle - Aleś Alachnovič; Julia Korosteleva (Center for Social and Economic Research (CASE), 2022)
The case of the Belarusian economy has puzzled many academic scholars for years. Belarus has often been referred to as a transition outlier, given its relatively fast recovery in 1996 and spectacular growth prior to the global financial crisis without much transformation of its economy. Three decades after gaining its independence, the state control of the economy still remains considerably high. Subsidized financing of state-owned enterprises allowed to preserve production capabilities over the first decade, achieve some productivity gains in the late 1990s-early 2000s, and to avoid social destabilization. However, with a delay in structural reforms, this economic model, also heavily dependent on the Russian subsidies and foreign debt, has become fatigue, driving the economy into stagnation in the 2010s. The Covid-19 pandemic, the 2020 post-presidential political crisis and Russia's war in Ukraine in 2022 put further strains on the economy, calling for change. This working paper will give an overview of the Belarusian economic developments before the presidential elections to have a better understanding of how various rigidities of the Belarusian economic model have amplified the detrimental effect of the political unrest for the economy and the Belarusian society overall, and will discuss the anticrisis and mid-term economic reforms Belarus will have to undergo.
Keywords: O11; O52; P21; P26; 330; Belarusian economic model; political crisis; economic reforms